A sustainable approach to scalable production of a graphene based flame retardant using waste fish deoxyribonucleic acid. (20th February 2020) - Zabihi, Omid; Ahmadi, Mojtaba; Li, Quanxiang; Ferdowsi, Mahmoud Reza Ghandehari; Mahmoodi, Roya; Kalali, Ehsan Naderi; Wang, De-Yi; Naebe, Minoo
Abstract: Graphene based flame retardants have gained increasing attention among researchers due to some interesting properties such as the tortuous path effect. Nonetheless, their complex, unsustainable, eco-unfriendly, and costly production hinder their adoption in various fields. Here, we used waste deoxyribonucleic acid, generated by the fishing industry, as a sustainable source of phosphorus and nitrogen to functionalize graphene nanomaterials. Our scalable and one-step approach, which employs waste-derived deoxyribonucleic acid as a green modifier in the ball milling process, is capable of producing the deoxyribonucleic acid-functionalized graphene nanoplatelets from graphite with high production yield, high oxygen, nitrogen and phosphorus contents, and high water dispersion concentration. Such a synthesized approach led to the exfoliated nanoplatelets, mostly consisting of layers with a thickness <9 nm and a lateral size of 300–600 nm, with the Brunauer–Emmett–Teller specific surface area of ∼180 m 2 /g. The remarkable effect of the deoxyribonucleic acid-functionalized graphene as an efficient and sustainable flame retardant on fire extinguishing of a wide range of polymer matrices including epoxy resin, polyvinyl alcohol, and polystyrene nanocomposites was successfully evidenced by achieving V-0 rating in UL-94 vertical burning tests. A multilayer char residue consisting of a compact layer and a porous layer was found to be the dominated mechanism in the fire extinguishing. The combination of deoxyribonucleic acid and graphene can result in manufacturing value-added green flame retardants from indirect reuse of fish waste, which can be suitable for high performance polymer nanocomposites including construction, automotive and aerospace. It is envisaged that the loop from fish waste to green flame retardants may come to be closed soon, which can be the main goal of the circular economy in cutting-edge applications. Highlights: Graphene in presence of waste fish DNA was exfoliated and functionalized. Highly DNA grafted graphene (GnP D ) contained ∼27% P, N, and O contents. GnP D acted as a strong flame retardant against polymer matrices. A compact layer and a porous layer were observed after polymers burning.